Structural Analysis of Leaf Spring (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Leaf springs are used in various types of commercial and private vehicles. The objective ofcurrent research is to optimize design of leaf spring using design of experiments. The modelling andFEA simulation is conducted using ANSYS simulation package. From the FEA simulation, the structuralcharacteristics of leaf spring is evaluated. Using optimal space filling design techniques, nine differentdesigns were generated with varying inner and outer radii. The smallest equivalent stress among thesedesigns was 88.84MPa, while the highest corresponding stress was 202.14MPa for design point number2.